DESIGNING MATHEMATICS PROBLEM BASED ON PISA TASK USING THE ETHNOMATHEMATICS CONTEXT (International Conference on Social and Islamic Studies, 2021)
This study aims to determine the procedure and assess the quality of developing mathematical problems using the ethnomathematics context. The method used was design and development research. The outcomes of this research were mathematical problems using the ethnomathematics context, which measured mathematics literacy ability. The content validity results based on the validator indicated that the test items were valid after being assessed using the content validity ratio and content validity index. In the reliability test, the mathematics problem using the ethnomathematics context was reliable. Based on the analysis results obtained, the average literacy ability of the students was in the medium category. Therefore, developing PISA-like mathematics problems using the ethnomathematics context as a learning resource could facilitate students learning mathematics.